Traditional Festive Culture of Tuva: Semantics and Transformation - Chochagaj N. Mongush, Chochagaj N. Mongush, Shenne B. Mainy, Natalya C. Damba, Shenne Y. Kuzhuget, Aniela B. Ondar,; Dolaana Sh.-o. Mongush, Syrga M. Mombey-ool, (Opción, 2019)
In this paper, various approaches to the definition of concepts tradition, traditional culture, celebration and festive culture are explored via general scientific methods such as comparative-historical, problem-logical and systemic. As a result of the research conducted in order to determine the specificity and nature of traditional festive culture the conceptual and theoretical aspects are specified. Semiotic aspects of Tuvan holidays and folk games are revealed; the latter in the study are understood as a meaning, a means aimed at the complete reproduction, storage and transmission of the culture of the Tuvan ethnos, its semantic core.